Capitalism : opposing viewpoints - Leone, Bruno, 1939- (St. Paul, Minn. : Greenhaven Press, 1986)
An anthology tracing the key elements of capitalistic theory and practice from Karl Marx to the present. Also includes opposing views on the relationship of capitalism and labor, the strengths and weaknesses of capitalism, its impact on the Third World, and its future.
Includes bibliographies and index.
Keywords: Capitalism -- Juvenile literature; Capitalism -- Juvenile literature